Facile synthesis of Ni5P4 nanosheets/nanoparticles for highly active and durable hydrogen evolution. (23rd March 2021) - Chen, Anyin; Fu, Liang; Xiang, Wenjun; Wei, Wei; Liu, Dan; Liu, Changlu
Abstract: It is essential to search highly active, steady and cheap non-noble electrocatalyst for hydrogen evolution reaction (HER). At present, nickel phosphides are extensively used in electrochemical hydrogen evolution due to its excellent stability and activity. Hence, we report a facile, effective and feasible strategy to synthesis of Ni5 P4 nanosheets/nanoparticles structure on carbon cloth, which was fabricated by electroless nickel plating on carbon cloth followed via straightforward thermal phosphidation treatment with NaH2 PO2 as phosphorus source. The as-prepared CC@Ni–P electrocatalyst exhibits HER activity with low overpotentials (93 mV vs. RHE) to attain current density 10 mA/cm 2 as well as small Tafel slope (58.2 mV/dec), which outperforms most nickel phosphides electrocatalysts. The excellent HER performance can be ascribed to the large electrochemically active surface area, and phosphorus-rich Ni5 P4 phase can supply further bridges sites of Ni and P. Significantly, as-prepared CC@Ni–P catalyst electrode exhibits no apparent HER activity decay after continuous stability test. Beyond that, the approach can be readily used to fabricate large size (5 × 5 cm) nickel phosphide electrocatalyst with excellent HER performance, which may be conducive to the proton exchange membrane (PEM) water electrolyser applications in future. This work opens an effective way to construct excellent performance transition-metal phosphides for HER. Graphical abstract: A facile, effective and feasible approach was demonstrated to produce high-performance nickel phosphide nanosheet/nanoparticle with efficient electrocatalytic hydrogen evolution reaction. Image 1 Highlights: A facile, effective and feasible approach to prepare Ni5 P4 was developed. Ni5 P4 composite exhibits an excellent HER activities. High ECSA and more Ni–P bridges sites account for the excellent HER performance. Ni5 P4 composite exhibited excellent long-term electrocatalytic stability.